A concatenated modified plus-minus 2^i (CMPM2I) photonic switching network - Rahman, M.M. Hafizur; Manjur, S.M. Ashif; Patwary, A.B.M. Kowser; Inoguchi, Yasushi (2012)
In this paper, we present a new photonic switching network. The proposed network is constructed by concatenating modified plus-minus 2^i and inverse modified plus-minus 2^i networks with two center stage overlapped. The performance is evaluated and compared with other networks to show the superiority of the proposed network over other networks. To construct the proposed network we require less number of switching elements. The proposed network yields less signal loss and first-order crosstalk, thus it scales well. The proposed network is a good choice for constructing photonic switch with low signal loss and cross talk.